2022
DOI: 10.3390/su14095548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Policy on Carbon Emission Reduction in Supply Chain under Uncertain Demand

Abstract: Although there are many articles on carbon emission reduction of sustainable supply chain, most of them study the carbon emission reduction efficiency of supply chain in the case of single carbon policy or demand determination. Based on previous studies, this paper considered a supply chain consisting of a single manufacturer and a single retailer in an uncertain demand market. The effects of demand randomness and different carbon policies on carbon emission reduction level and optimal decision in supply chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Building upon the comparison of the two policies, refs. [23,24] introduced a third policy for comparison. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon the comparison of the two policies, refs. [23,24] introduced a third policy for comparison. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, ref. [24] compared carbon tax, carbon trading, and government subsidies, noting that carbon tax may reduce supply chain profits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He et al [ 25 ] made the optimal decisions of channel members under carbon cap and trade policy through MV approach. Li et al [ 26 ] studied manufacturer-led supply chain with carbon cap and trade by constructing mean-variance utility function, they pointed out that a low degree of risk avoidance will increase firms’ profits. Choi et al [ 27 ] considered risk averse agents and retail competition under MV framework, and showed that the increasing or decreasing the retail selling price depends on the level of competition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the aforementioned theoretical analysis, considering the research conclusions of Fan et al (2016), Song et al (2019), andLi et al (2022), the government and enterprises should follow their own maximizing goals of carbon decision behavior. The government expects to reduce carbon emissions through the increasing costs of enterprises for environmental performance, while enterprises want maximum profits for corporate performance to cut down their total costs through many more production with carbon emissions.…”
Section: Critical Factors Of Carbon Decision Behaviormentioning
confidence: 99%